Sikap Masyarakat Tani terhadap Pengembangan Kampung Kelor di Desa Kedungbulus Kecamatan Gembong Kabupaten Pati - Agnas Wardhani; Suwarto Suwarto; Sugihardjo Sugihardjo (Universitas Sebelas Maret, 2019)
The aims of this research are to analyze farmer’s attitudes towards the development of Kampung Kelor; analyzing the relationship between age, formal education, land tenure, non formal education, farming experience, and the influence of others who are considered important towards the development of Kampung Kelor; and differentiating the attitude of farming communities that have and have not tried kelor. The research employed a quantitative method by a survey technique. The research location was Kedungbulus Village with the consideration of Kedungbulus Village, is the only producer of Moringa processed products in Pati Regency which has a production permit for Household Industry (PIRT) and related research and assists the process of making Moringa. The samples were taken by proportional random sampling technique. The data analysis that used is Rank Spearman and U Mann Whitney with the SPSS 20.0 program application for Windows. The results of the study showed that: Farmer’s attitudes towards the development of Kampung Kelor (increasing income, educating the community, advancing villages, and increasing food and nutrition security) are good included in the agreed category; the forming factors of community attitudes are significantly related to the farmers attitudes are age (X1), formal education (X2), non-formal education (X4), farming experience (X5), and the influence of others who are considered important (X6), meanwhile the land tenure (X3) is not significantly related; Farmers who have cultivated moringa have a better attitude than farmers that have not cultivated moringa.